2022
DOI: 10.3390/fishes7020078
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol Attenuates High-Fat-Diet-Induced Oxidative Stress, Apoptosis and Inflammation of Blunt Snout Bream (Megalobrama amblycephala) through Its Regulation of Mitochondrial Homeostasis

Abstract: The present study was conducted to investigate the effects of dietary hydroxytyrosol (HT) on oxidative stress, inflammation and mitochondrial homeostasis in blunt snout bream (Megalobrama amblycephala). Fish were fed a low-fat diet (LFD, 5% lipid), a high-fat diet (HFD, 15% lipid), an LFD supplementing 200 mg/kg HT, or an HFD supplementing 200 mg/kg HT. After 10-week feeding, significant reduction of growth was observed in fish fed HFD, compared with other groups. HFD caused oxidative stress and more apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…High fat intake could cause excess fat accumulation and induce oxidative stress in fish [ 27 , 32 ]. Moreover, the the activities of antioxidative enzymes (CAT, SOD, and GSH-PX) decreased, and then, peroxidation occurred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High fat intake could cause excess fat accumulation and induce oxidative stress in fish [ 27 , 32 ]. Moreover, the the activities of antioxidative enzymes (CAT, SOD, and GSH-PX) decreased, and then, peroxidation occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time quantitative PCR (qPCR) was conducted in accordance with the method described in our recent study [ 27 ]. The primer sequences used in the present study were shown in Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, hydroxytyrosol (HT), a kind of polyphenol with a small molecular weight, is the most efficient antioxidant in olives and is considered a mitochondrial nutrient. It is reported that adding HT to diets can relieve oxidative stress, apoptosis, and inflammation, likely due to its regulation of mitochondrial homeostasis [5].…”
Section: Fish Nutrition and Physiologymentioning
confidence: 99%
“…However, in blunt snout bream (Megalobrama amblycephala), TG content of primary hepatocytes (treated with oleic acid to induce lipid accumulation) was decreased by HT in a dose-dependent manner (2.5, 5 and 10 µM) [19]. In the same species, but from an in vivo perspective, a HFD (15% lipid) with 100 mg/kg HT supplementation reduced hepatic fat deposition [19], and the same diet but with 200 mg/kg HT reduced reactive oxygen species (ROS) content and mitochondrial dysfunction in the same tissue [20]. Moreover, in a previous study by our group, a decrease in head and viscera adiposity was observed in zebrafish (Danio rerio) larvae exposed to 100 µM HT in the water [21].…”
Section: Introductionmentioning
confidence: 97%